Photo-induced biosynthesis of silver nanoparticles using aqueous extract of Erigeron bonariensis and its catalytic activity against Acridine Orange - Kumar V.; Singh D.K.; Mohan S.; Hasan S.H. (My University, 2025)
The green synthesis of silver nanoparticles (AgNPs) has reduced the pollution load in the environment to a greater extent by avoiding the use of hazardous chemicals. In the present work we have developed an ecofriendly and zero cost approach for the green synthesis of more stable and spherical AgNPs using aqueous extract of Erigeron bonariensis (AEE) which act as both reducing and stabilizing agent. The reaction of AEE and AgNO3 was carried out in direct sunlight for the instant biosynthesis of AgNPs within minutes. The biosynthesis was monitored by UV-vis spectroscopy which exhibited a sharp SPR band at 442 nm and 435 nm after 5 and 35 min of sunlight exposure. The optimum conditions for biosynthesis of AgNPs were found to be 2.5 mM AgNO3 concentration, 1.5% (v/v) of AEE inoculum dose and 35 min of sunlight exposure. Presence of spherical AgNPs with average size 13 nm was confirmed by SEM and TEM analysis. The XRD and SAED analysis confirmed the crystalline nature of the AgNPs where the Bragg's diffraction pattern at (111), (200), (220) and (311) corresponded to face centered cubic crystal lattice of metallic silver. The average roughness of the synthesized AgNPs was 3.21 nm which was confirmed by AFM analysis. FTIR analysis was recorded between 4000 and 400 cm- 1 which confirmed the involvement of various functional groups in the synthesis of AgNPs. The AgNPs thus obtained showed catalytic activity towards degradation of Acridine Orange (AO) without involvement of any hazardous reducing agent. The concentration dependent catalytic activity of the synthesized AgNPs was also monitored using 1, 2 and 3 mL of silver colloids and was found that the degradation of AO followed pseudo first-order kinetics. © 2015 Elsevier B.V. All rights reserved.